Sertifikasi Halal Untuk Penguatan Branding Produk Usaha Mikro Kecil di Kabupaten Pasuruan - Aslikhah; Alimatul Farida (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
Since the enactment of the Halal Product Guarantee Law on Micro, Small and Medium Enterprises (MSMEs), the number of MSMEs that are halal-certified in Pasuruan Regency has experienced a rapid increase. This situation indicates that the halal certification of MSME products has an important position in society. The purpose of this study was to find out Halal Certification for Strengthening Product Branding of Micro, Small and Medium Enterprises in Pasuruan Regency. The research method used is qualitative research with an instrumental case study approach because you want to understand or emphasize an understanding of an issue or reformulate a theoretical explanation. Data collection was carried out by observation, interviews and documentation. The analysis in this study uses qualitative data analysis, and the results of this study emphasize meaning rather than generalization. The stages in this research were first, formulating the problem as the focus of research, second, collecting data in the field, third, analyzing data, and fourth formulating the results of a study on Halal Certification for Strengthening MSME Product Branding in Pasuruan Regency. The results showed that the halal certification of MSME products in Pasuruan Regency did not yet have the power of branding from consumer perceptions, due to several indicators, namely brand awareness, brand associations, perceived quality and consumer brand loyalty. MSME products that are halal certified are still low. The low level of these indicators is due to differences in education levels, environmental conditions, and low knowledge of halal certification.